The association between GP organisational factors and the effectiveness of a prevention programme for cardiometabolic diseases: a prospective intervention study - Ilse F Badenbroek; Daphne M Stol; Markus MJ Nielen; Monika Hollander; Niek J de Wit; François G Schellevis (BJGP Open, 2020)
Background: Owing to the rising disease burden of cardiometabolic diseases (CMD), prevention programmes for CMD are increasingly implemented in primary care. Organisational practice characteristics and availability of preventive services may be associated with a more effective programme. Aim: To identify possible organisational success factors from general practices related to an effective primary prevention programme for CMD. Design & setting: A prospective intervention study involving 37 Dutch general practices was undertaken. Method: Patients aged 45–70 years without known CMD, hypertension, or hypercholesterolemia were invited for the prevention programme. The outcome measures were an improvement (yes/no) in four different CMD risk factors between baseline and 1-year follow-up on an individual level (body mass index [BMI], smoking, systolic blood pressure, and cholesterol ratio). Multivariate logistic regression analysis was used for assessing associations between practice organisational characteristics and outcomes. Results: Just over half of the participants showed an improvement on one or more risk factors. Marginal differences were found in the four different outcomes between the practices with different organisational characteristics. None of the practice characteristics that were tested showed a significant association with an improvement in one of the outcome measures. Conclusion: In this study, general practice organisational and preventive service characteristics showed no impact on the effectiveness of a CMD prevention programme. Possible explanations could be the effectiveness of protocolised pharmaceutical treatment and only limited contribution of lifestyle programmes on the improvement of CMD risk factors.